Telmisartan Improves Insulin Resistance: A Meta-Analysis. (November 2018) - Wang, Yan; Qiao, Shun; Han, De-Wu; Rong, Xin-Ren; Wang, Yi-Xiao; Xue, Jing-jing; Yang, Jing
Abstract : Background: Diabetes mellitus, metabolic syndrome, and other obesity-related diseases are characterized by insulin resistance (IR) as a common pathophysiological change and are closely related to cardiovascular disease, which seriously threaten human health. Telmisartan belongs to a group of drugs called angiotensin II receptor antagonists (ARBs) and it can partially activate peroxisome proliferator–activated receptors. Animal experiments have confirmed that telmisartan can regulate glucose and lipid metabolism, and improve IR. Study Question: This study performs a systematic review of the advantages of telmisartan in improving IR and compared it with other ARBs. Study Design: Randomized controlled trials (RCTs) that compared telmisartan with other ARBs in patients with obesity, diabetes, impaired glucose tolerance, and metabolic syndrome were searched from PubMed, EMBASE, the Cochrane Library, China National Knowledge Infrastructure, Wan Fang Database, and Chinese biomedical literature database (CBM). RCTs published as of the end of April 2017 were included in the present study. Measures and Outcomes: The outcomes included homeostasis model assessment of insulin resistance, fasting blood glucose level, fasting insulin level, diastolic blood pressure, and systolic blood pressure. We used a fixed-effects model or random-effects model to pool the estimates according to the heterogeneity between the included studies. Results: A total of 21 RCTs, which included 1679 patients, were included. Results revealed that telmisartan was superior in improving homeostasis model assessment of insulin resistance (mean difference = −0.23, 95% confidence interval [CI], −0.40 to −0.06), reducing fasting blood glucose level (mean difference = −0.32, 95% CI, −0.57 to −0.07), reducing fasting insulin level (mean difference = −1.01, 95% CI, −1.63 to −0.39), and decreasing diastolic blood pressure (mean difference = −1.46, 95% CI, −2.10 to −0.82) compared with other ARBs. However, for the decrease in systolic pressure, the difference was not statistically significant (mean difference = −0.73, 95% CI, −1.53 to 0.07). Conclusion: Telmisartan can better improve IR compared with other ARBs.